2008
DOI: 10.7863/jum.2008.27.11.1623
|View full text |Cite
|
Sign up to set email alerts
|

Placenta Accreta

Abstract: Objective. Placenta accreta is a life-threatening problem that is rising in incidence in the developed world. The increased risk of placenta accreta in women with placenta previa and 1 or more prior cesarean deliveries is well established and prompts careful sonographic evaluation. Our objective was to emphasize that accreta is also identified at sites other than cesarean scars. Methods. Two cases of placenta accreta without placenta previa seen in association with uterine scarring from myomectomy and uterine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Placenta praevia [3], [4], [13], [16], previous caesarean delivery [3], [4], [13], [17], [18], other previous uterine surgery [13], [19], [20], multiparity [13], [20], advanced maternal age [3], [4], [13], [16], hypertensive disorders [17], smoking [17], IVF pregnancy [21] and a female fetus [22] are all factors that have previously been suggested as being associated with a higher risk of placenta accreta/increta/percreta. Our study investigated each of these factors and found that the risk of placenta accreta/increta/percreta was independently increased in women with a previous caesarean delivery; in women with other previous uterine surgery; in women with an IVF pregnancy and in women with placenta praevia diagnosed antepartum.…”
Section: Discussionmentioning
confidence: 99%
“…Placenta praevia [3], [4], [13], [16], previous caesarean delivery [3], [4], [13], [17], [18], other previous uterine surgery [13], [19], [20], multiparity [13], [20], advanced maternal age [3], [4], [13], [16], hypertensive disorders [17], smoking [17], IVF pregnancy [21] and a female fetus [22] are all factors that have previously been suggested as being associated with a higher risk of placenta accreta/increta/percreta. Our study investigated each of these factors and found that the risk of placenta accreta/increta/percreta was independently increased in women with a previous caesarean delivery; in women with other previous uterine surgery; in women with an IVF pregnancy and in women with placenta praevia diagnosed antepartum.…”
Section: Discussionmentioning
confidence: 99%
“…No differences in the rate of breech presentation between the groups have been found in the present study. Placenta accreta has been reported to be a possible complication of uterine surgery such as hysteroscopic myomectomy and lysis of intra uterine synechiae [ 26 ]. No study in the literature reports any case of placenta accreta or increta after metroplasty, and no case has been observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the conclusions of relevant studies show that this concern is unnecessary [28,29] . One endometrial regeneration cycle should be su cient to allow embryo implantation [30] .…”
Section: Discussionmentioning
confidence: 99%